Limitations to Inclusive Unions from the Perspectives of White and Aboriginal Women Forest Workers in the Northern Prairies - Mills, Suzanne E (Just Labour, 2007)
Several authors have argued that broadening the traditional understandings of union solidarity is necessary for union renewal. Concerns specific to workers from marginalized groups have been shown to challenge traditional understandings of union collectivity. This paper draws on interviews with white and Aboriginal women forest processing workers to argue that interrogating marginalized workers' negative representations of their unions can provide insights that will help to broaden traditional understandings of union solidarity. I use thematic analysis followed by critical discourse analysis to examine women workers' negative talk about unions. I present examples of how women's negative representations of their unions can be understood as different forms of collectivism when examined in the context of their lived experiences of work and unionism. Some white and Aboriginal women's representations of their unions wove individualistic anti-union statements together with their previous experiences of work highlighting the inequality between unionized and non-unionized workers in the community. The talk of other Aboriginal women critiqued the union for not representing them while demonstrating a sense of collectivity with other Aboriginal workers. By exploring linkages between women's negative representations of unions and their work experiences, unions can better understand the negative union sentiment of marginalized workers and use this to create more inclusive forms of solidarity.